Loneliness and Daily Alcohol Consumption During the COVID-19 Pandemic. (20th August 2021) - Bragard, Elise; Giorgi, Salvatore; Juneau, Paul; Curtis, Brenda L
Abstract: Aims: This pilot study aimed to identify associations of loneliness and daily alcohol consumption among US adults during the Coronavirus Disease-2019 pandemic. Method: Participants completed daily assessments for 30 days. Results: Results suggest people who feel lonelier on average drink more alcohol, however, people who feel lonelier than usual drink less. Conclusion: Findings highlight the need to disaggregate within- and between-person components of alcohol use.